Gaya Hidup dan Stigma Sugar Baby di Indonesia - Dyan Paramitha Darmayanti; Mahmud Tang; Pawennari Hijjang (Universitas Lambung Mangkurat, 2024)
This study aims to find out more about the phenomenon of sugar baby relationships, especially in terms of material exchange and financial support provided by sugar daddy. The research method used was observation and in-depth interviews using a qualitative perspective and involving seven informants. The results of this study found that there are four types of sugar babies based on their motivations, namely traditional sugar baby, pragmatic sugar baby, mentorship sugar baby and escort or transactional sugar baby. In becoming a sugar baby, there are several aspects that change not only in terms of economic, social but also individual behavioral attitudes